2005
DOI: 10.1128/jvi.79.22.14079-14087.2005
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Capture Microdissection: Refining Estimates of the Quantity and Distribution of Latent Herpes Simplex Virus 1 and Varicella-Zoster Virus DNA in Human Trigeminal Ganglia at the Single-Cell Level

Abstract: Herpes simplex virus type 1 (HSV-1) and varicella-zoster virus (VZV) establish lifelong latent infections in human sensory ganglia, processes that have been investigated extensively but are still not fully elucidated. It is well established that during latency, infectious HSV-1 and VZV particles are not produced (40,41,56), but small subsets of their genes are expressed (11,12,13,21,25,27,31,35,44,52). These latent viruses, however, are subject to single or multiple rounds of reactivation and can result in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
107
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 58 publications
8
107
1
Order By: Relevance
“…Since blood type A individuals comprise 30 to 40% of the population, our findings help explain reports that VZV protein expression during latency is common, whereas others have found that VZV protein expression is rare (7,13,15,16,25,32). The MAG artifact may also contribute to the discrepancy between reports of high frequencies of neurons that express VZV proteins and the low frequency of neurons that contain VZV genomes based on LCMD and quantitative PCR (19,29). In addition to the presence of neuronal pigments and immunological cross-reactivity between IE62 and neuron-specific brain-derived neurotrophic factor (BDNF), this report identifies an important new variable that confounds the accurate detection of VZV proteins in sensory neurons (8,32).…”
Section: Demonstration Of Mag Reactivity In Human Neuronal Golgi Zonescontrasting
confidence: 51%
See 1 more Smart Citation
“…Since blood type A individuals comprise 30 to 40% of the population, our findings help explain reports that VZV protein expression during latency is common, whereas others have found that VZV protein expression is rare (7,13,15,16,25,32). The MAG artifact may also contribute to the discrepancy between reports of high frequencies of neurons that express VZV proteins and the low frequency of neurons that contain VZV genomes based on LCMD and quantitative PCR (19,29). In addition to the presence of neuronal pigments and immunological cross-reactivity between IE62 and neuron-specific brain-derived neurotrophic factor (BDNF), this report identifies an important new variable that confounds the accurate detection of VZV proteins in sensory neurons (8,32).…”
Section: Demonstration Of Mag Reactivity In Human Neuronal Golgi Zonescontrasting
confidence: 51%
“…In autopsied human ganglia, the frequency of individual VZV-positive neurons was 1.0 to 6.9% by single-cell laser capture microdissection (LCMD) and PCR (29). However, immunostaining analyses of VZV protein expression in latently infected neurons have differed significantly.…”
mentioning
confidence: 99%
“…In the ocular model, mice that survive have no apparent replicating virus in DRG or trigeminal ganglia four to six weeks after infection (10,36,40,41). However, the frequency of infected ganglion cells in murine models is much lower than the estimate of 2 to 10.5% from human autopsy studies (42). The different outcomes of infection of human and mouse ganglia in vivo are likely to reflect adaptations of HSV-1 to its natural host.…”
Section: Discussionmentioning
confidence: 69%
“…By in situ hybridization and PCR methods, VZV DNA has been reported in as few as 1.5% of neurons exclusively (none in satellite cells) to as many as 30% of ganglion cells (neurons as well as satellite cells) (24,26). Most recently, Wang et al used a laser-capture microdissection/PCR method to provide more precise information at the single-cell level by examining 1,722 neurons in trigeminal ganglia (TGG) from seven individuals (49). These experiments identified VZV DNA in 4.1% of neurons (range, 1.0 to 6.9%) (49).…”
mentioning
confidence: 99%